Protected areas:: limits and contributions to nature conservation - Maganhotto, Ronaldo Ferreira; Santos, Leonardo José Cordeiro; Nucci, João Carlos; Lohmann, Marciel; Souza, Luiz Claudio De Paula (Sustainability in Debate, 2014)
The environmental crisis emerges mainly in the 70s contributing to the legitimacy of protected areas, through the creation of conservation units (legally protected areas). However, difficulties related to lack of resources, lack and/or inconsistency of management plans and environmental zoning contrasts, sometimes the fulfillment of the objectives set for these units. The objective of this paper is to present the possibilities and limitations related to the conservation units, discussing issues related to laws governing them and the limitations and proposals for the management plan. The methodological basis was based on documentary and bibliographical research showing that the success of conservation depends, largely, on the articulation of the actions promoted by the various actors involved in the process, by strengthening and/or implementation of management plans, as well as specific measures such as avoiding deforestation and integration of UC's to the local economy.